Confinement model for FRP confined normal- and high-strength concrete circular columns - Pham, Thong; Hadi, M. (2014)
This study establishes a confinement model for FRP confined normal- and high-strength concrete circular columns. A new column parameter was suggested for estimating the compressive strength of FRP confined concrete. The proposed model is able to predict the ultimate condition of FRP confined concrete columns that have similar unconfined concrete strength and confining pressure but significant differences in the jacket stiffness. The proposed model was then verified using a database of 574 FRP confined concrete circular columns with different types of FRP. This database covers unconfined concrete strength between 15 MPa and 170 MPa and specimens with a diameter ranging from 51 mm to 406 mm. Furthermore, this database includes specimens with a variety of FRP types: carbon FRP (CFRP), glass FRP, high-modulus carbon FRP, aramid FRP (AFRP), CFRP tube, ultra-high-modulus CFRP tube, and AFRP tube. Finally, the model's prediction fits the experimental results very well by verifying the proposed model with the extensive database. © 2014 Elsevier Ltd. All rights reserved.